Kaji Eksperimental Standby Mode Beban 1000 WATT Pada Residential Air Conditioning Hibrida Sebagai Penyejuk Udara Ruangan Dan Pemanas Air/Pengering - Dicky Ikhwandi; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In the Air Conditioning engine, the resulting cooling effect is used to cool the room and the heat effect that is simply thrown into the environment. While, the Hybrid Residential Air Conditioning machine is utilizes the cooling effect and the simultaneous heating effect of the refrigeration machine. Chiller is a cooling system that uses cooling media (water or brine) and HCR-22 as a working fluid. The purpose of this study is to determine the consumption of electrical energy, by using standby mode method with 1000 Watt cooling load in this research got the average value Coefficient Of Performance (COP) of 2.471, average value Performance of Factor(PF) of 3.43, average value Total of Performance (TP) of 5.90. For the average temperature in the cooling chamber is 28.20 0C, the average temperature in the heating chamber is 44.64 0C, with an average compressor power of 1.2680 kW and electricity consumption in 2 hours of working of 2.5359 kWh.Keywords: Air Conditioning, Hybrid Residential, Chiller, Performance, Temperature, Compressor, Electricity.